A dynamic mechanism for determining relationships in a partially ordered user hierarchy. (3rd April 2006) - Chang, Chin-Chen; Lin, Iuon-Chang; Tsai, Hui-Min
In this paper, we propose a mechanism in the partially ordered user hierarchy, instead of the tree hierarchy discussed till now, by assigning each user an interpolating polynomial constructed from the user's own id number and his fathers'. In this way, any two users' relationship can be quickly determined from evaluating their associated polynomials. Moreover, whenever a new user is added to or deleted from the user hierarchy, none or only some relevant polynomial needs to be updated, differing from the previously proposed schemes where the information needs to be reconstructed all over.